Electrolytes for better and safer batteries: Liquid, solid or frameworked, what's next? - Jianguo Sun; Hao Yuan; Jing Yang; Yong-Wei Zhang; John Wang (Next Materials, 2023)
Looking back on the short and yet very rewarding history that has shaped the game-changing lithium-ion batteries over the past three decades, among the main technical milestones and on-going challenges are the energy density, cycling-ability and yet poor safety, which are largely related to the use of organic liquid electrolytes. While the holey grail for energy storage is all-solid-state batteries, there is the inevitable transition from liquid electrolytes to solid ones, in the long term. Nevertheless, currently known solid-state electrolytes face problems of their own and also the largely incompatible interfaces with the solid electrodes. Then an interesting question arises: At least in the near-future term, what would be the electrolytes that can replace the organic liquid electrolytes? In this short Comment, we examine the transition from liquid electrolytes to solid states, where a potential newcomer is the frameworked, which is expected to address the sluggish kinetics of ion transport and poor interfaces with solid electrodes.